Big ships on the horizon and growing fragmentation at home. Genoa’s transformation of the urban landscape - Hillmann, Felicitas (ERDKUNDE, 2008)
In 1986 Genoa was a city in decline. The ailing port and heavy industry on the western outskirts defined the city. There was little tourism. By 2006 Genoa could present itself as a fresh and modern European city, the vertical city structure had been enhanced, the old port transformed into a tourist magnet. The elements of this reconstituted urbanity resemble a facsimile of modern Europe as portrayed in the urban developers’ trade journals. Outside impulses prompted Genoa onto this path of development, as well as the endogenous potentials that led to the accumulation of already existing resources. It will be shown that the strategies adopted for urban development in Genoa relied to a great extent on new forms of urban governance and that there was a strong notion of tradition and a clear path dependency in the way the urban landscape was reinvented. The adopted instruments of strategic planning neglected the problem areas of internal social fragmentation and immigration, two aspects which have become more important accompanying the process of urban renewal. The restructuring of the port turns out to be of central importance in understanding Genoa’s urban transformation. It is the lifeline which links Genoa to the containerized global circuits and frames the urban renewal.